PENGETAHUAN PENGELOLAAN SAMPAH SEBAGAI SUMBER BELAJAR PENDIDIKAN KARAKTER SISWA SD MENURUT PERSPEKTIF ISLAM - Ahmad Gunadi (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2019)
ABSTRACT: Waste, by definition, is something that is dirty and must be disposed of and consisting of organic or non-organic materials. If it is not processed and managed properly it can cause illness and disaster. An Organic waste can be processed and managed into compost which is beneficial for human life. The aim of the study was to increase student knowledge of waste as a source of learning for character education. Research method: qualitative descriptive. Research respondents for third grade students of public elementary schools. Data collection techniques: observation, interviews, field notes, and documentation. The results of the study: 1) 38 students stated that waste can be used as a learning resource for character education; 2) 38 students stated that character education can be done by parents, teachers, and the community by giving examples of good and right behavior and attitudes when disposing and utilizing waste; 3) 39 students stated that efforts to reduce floods could be avoided by accustoming everyone to disposing of garbage in its place; 4) 37 students know organic and non-organic waste. Conclusion: Through the learning process of character education, waste can be used as a learning resource and can be processed and managed into economically valuable compost, which in the end can also help reduce floods that often occur in the community.